Interactions of solutes with crystal defects: A new dynamic design parameter for advanced alloys. (15th March 2021) - Kontis, Paraskevas
Abstract: Pushing the performance limits of engineering systems aiming to enhance their efficiency and reduce emissions for a sustainable future requires new materials. Current alloy design strategies consider alloys as static systems, but their microstructure and composition continuously evolves in operando. This viewpoint is concerned with a new alloy design dynamic parameter that arises from information pertaining to the interactions of solutes with crystal defects obtained at the near-atomic scale. Recent technological breakthroughs in high-resolution characterization have enabled structural and compositional imaging at near-atomic scale providing new insights into such interactions. The role of these interactions on the continuously evolving microstructure and composition that governs failure in high temperature alloys, such Ni-, Co-based alloys and Ti-alloys is discussed. The development of a solute-defect database that accounts for these interactions, aiming to more accurately predict the mechanical performance of current and new alloys is necessary for more dynamic alloy design strategies. Graphical abstract: Image, graphical abstract